2013
DOI: 10.1111/jdi.12142
|View full text |Cite
|
Sign up to set email alerts
|

Sitagliptin improves albuminuria in patients with type 2 diabetes mellitus

Abstract: The aim of the present study was to determine the effect of sitagliptin on microalbuminuria in patients with type 2 diabetes mellitus. Materials and Methods: A total of 85 patients with type 2 diabetes mellitus (age >20 years, <80 years, hemoglobin A1c [HbA1c] <8.4%) were randomized to patients taking sitagliptin 50 mg or other oral glucose-lowering agents. The following parameters were evaluated at 0, 3 and 6 months after the treatment: bodyweight, blood pressure, HbA1c, fasting plasma glucose, fasting plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 30 publications
3
74
0
5
Order By: Relevance
“…Diabetic nephropathy might have progressed in Study 2 since patients of the switch-to-vildagliptin group with poor urinary albumin excretion had elevated blood pressure at 24 weeks. Other possible reasons for the difference in the results of Study 1 and Study 2 include a small sample size; short follow-up period; and the data used for Study 2 were those of switching from sitagliptin to vildagliptin, in which we have reported that sitagliptin was effective in reducing microalbuminuria [20]. Based on the above comparison, we think that our results indicate that urinary albumin excretion improved only in DPP-4 inhibitor-naive patients treated with vildagliptin at 100 mg daily.…”
Section: Discussionmentioning
confidence: 98%
“…Diabetic nephropathy might have progressed in Study 2 since patients of the switch-to-vildagliptin group with poor urinary albumin excretion had elevated blood pressure at 24 weeks. Other possible reasons for the difference in the results of Study 1 and Study 2 include a small sample size; short follow-up period; and the data used for Study 2 were those of switching from sitagliptin to vildagliptin, in which we have reported that sitagliptin was effective in reducing microalbuminuria [20]. Based on the above comparison, we think that our results indicate that urinary albumin excretion improved only in DPP-4 inhibitor-naive patients treated with vildagliptin at 100 mg daily.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, human clinical studies reported that sitagliptin had reduced albuminuria in many T2DM patients with nephropathy [39][40][41][42]. When sitagliptin was administered, the bigger reduction of urinary albumin was observed in the cases who had the greater albuminuria at the baseline [40].…”
Section: Discussionmentioning
confidence: 99%
“…Such combination therapy should put in to trial in human subject, instead of sitagliptin linagliptin combined with CoQ10 Should be tried since study suggest linagliptin does not require dose adjustment and also restore the physiological balance of VEGF. [219,220] …”
Section: Inhibitorsmentioning
confidence: 99%